Angst im neuen Wohlfahrtsstaat: kritische Blicke auf ein diffuses Phänomen - Betzelt, Sigrid; Bode, Ingo (HWR Berlin Forschung, 2018)
Of late, media coverage of anxiety and insecurity proliferating among the German population has been considerable. However, the social sciences have only recently explored these tendencies more profoundly, e.g. with respect to fears about social decline among the middle classes or immigration conflicts. Yet what are the interdependencies between the dynamics of fear and welfare state change? How do these tendencies connect with altered living conditions and the recalibration of programmes and institutions? Have recent reforms provoked anxiety instead of taming it? How do citizens perceive and cope with it, and with what impact in terms of social cohesion?This edited volume offers the first answers to these questions. Its focus is on overarching institutional and political developments, on the one hand, and distinctive areas of social protection as well as problems related to migration, unemployment, family and youth policy, and old age provision, on the other.With contributions bySigrid Betzelt, Ingo Bode, Silke Bothfeld, Christine Burmeister, Christoph Burmeister, Florian Engel, Carolin Freier, Vincent Gengnagel, Thomas Gurr, Marlene Haupt, Jan-Ocko Heuer, Brigitte Loose, Ralf Lüth, Steffen Mau, Dorothea Schmidt, Tanja Schmidt, Andreas Schmitz, Nadine Schöneck-Voß, Carsten Schroeder, Werner Sesselmeier, Reinhold Thiede, Aysel Yollu-Tok, Franz Zahradnik